Implementation of school-based management in improving early childhood education quality standards - Luluk Elyana; Muniroh Munawar (Jurnal Konseling dan Pendidikan, 2025)
This research addresses the challenges in enhancing early childhood education (ECE) quality standards through the application of School-Based Management (SBM). Despite widespread recognition of the importance of SBM in educational settings, many schools, especially in early childhood education, struggle to meet established quality standards due to limited decision-making autonomy, inadequate leadership, and insufficient community involvement. The research problem revolves around the gap in understanding how SBM can be effectively applied to improve ECE standards, particularly in decentralized school systems. The study aims to investigate the key factors influencing the successful implementation of SBM in early childhood education, focusing on leadership engagement, teacher involvement, community participation, and alignment with quality standards. Using a qualitative literature review approach, the analysis synthesizes data from academic articles, reports, and case studies published in the past decade. Key factors identified through thematic content analysis highlight the importance of decentralized decision-making in improving educational outcomes. The findings suggest that SBM can lead to measurable improvements in educational practices, resource allocation, and community engagement when implemented effectively. Specifically, leadership autonomy, teacher involvement in decision-making, and active community participation are critical drivers for enhancing ECE quality. These results provide actionable insights for policymakers and school administrators to tailor SBM implementation strategies, ensuring that they align with both local needs and established national and international quality standards. This study contributes to the academic understanding of SBM’s role in early childhood education, offering practical recommendations for policy reforms and school management practices aimed at improving ECE quality through decentralization.